Cobalt‐Catalyzed C−H Functionalizations by Imidate Assistance with Aryl and Alkyl Chlorides. Issue 15 (8th July 2016) - Mei, Ruhuai; Ackermann, Lutz
Abstract: A catalytic system comprising the inexpensive cobalt(II) acetylacetonate [Co(acac)2 ] and an N‐heterocyclic carbene (NHC) ligand enabled versatile C−H arylations by oxazoline assistance. The broadly applicable, low‐valent cobalt catalyst displayed a wide substrate scope, and even proved applicable to challenging C−H alkylations with β‐hydrogen‐containing primary and secondary alkyl chlorides. The power of the cobalt‐catalyzed C−H arylation protocol was among others reflected by facile C−H activation at a room temperature of 23 °C, and efficient late‐stage diversification, providing access to bioactive biaryls. Abstract :